Clinical preceptorship in pharmacy workshop: Mastering good preceptor traits for effective learning / Nurulfalahin Daud @ Ibrahim and Associate Prof. Dr. Mahmathi Karuppannan - Daud @ Ibrahim, Nurulfalahin; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Preceptorship is a short-term training between learner and preceptor, who provides individual attention to the learning needs and performance feedback of the learner for further improvement. As one of the efforts to enhance teaching skills so that students have a positive learning experience in clinical pharmacy field, several pharmacy lecturers (Ms Izzati Abdul Halim Zaki, Ms Zakiah Mohd Noordin, Ms Nurulfalahin Daud @ Ibrahim, Ms Nik Aisyah Najwa Nik Mustaffa Shapri, Mdm Nik Ateerah Rasheeda Mohd Rocky, and Mdm Saliha Azlan) attended Clinical Preceptorship in Pharmacy, an engaging workshop, organized by Faculty of Pharmacy, Universiti Kebangsaan Malaysia (UKM). The workshop, held on 28th August 2023, was attended by practicing pharmacists, pharmacy lecturers, and health science educators. This enabled opportunities for networking and the exchange of information within the broader scope of pharmacy and health science disciplines. The aim of the workshop was for participants to learn about competency standards, roles, and code of ethics as preceptors; design a competency-based clinical learning experience incorporating clinical reasoning skills and models of behaviour; plan effective bedside teaching and student preparation; and conduct effective formative and summative assessments. These goals were achieved through interactive exchanges between the speaker and participants. The workshop speaker, Prof. Dr. Mohamad bin Makmor Bakry, gave an insightful talk regarding clinical pharmacy and pharmaceutical care practice, emphasizing the clinical teaching delivery to enhance students clinical reasoning skills. He also emphasized the importance of teaching and learning philosophy as the foundation of teaching methodology. One can adhere to any philosophy, but it must be relevant to the course one needs to teach. Besides, as generations change, teaching styles and the appropriateness of information processing should evolve.